HUBUNGAN MANAJEMEN KELAS TERHADAP HASIL BELAJAR SISWA SD NEGERI 4 MADE KECAMATAN LAMONGAN KABUPATEN LAMONGAN - Kuswanto, Kuswanto; Youhanita, Ety; Eryadini, Ninies; Astutik, Nur Fithria Wiji (Jurnal Manajemen Pendidikan, 2023)
Education is a complex activity, has broad dimensions and many variables that influence it. As a psychological process, education cannot be separated from teaching and learning activities. Thus, education is a process of interaction between educators and students who have specific goals. Education as a process basically guides students towards the stages of maturity in which education is in the family and in the environment. Classroom management is one of the teacher's knowledge and skills concerning the creation of conducive, effective classroom conditions in order to achieve optimal learning goals. Given this, most of the teachers who teach in the classroom do not pay attention to classroom management. In fact, one aspect of achieving learning objectives is classroom management. This research is a correlational study which aims to investigate the relationship between classroom management (X) and student learning outcomes (Y). Data collection techniques are methods used by researchers to obtain data discussed in research. Research data was collected through various methods including: questionnaires, interviews, observation, and documentation. The results showed that there was a positive and significant relationship between classroom management and student learning outcomes at SD Negeri 4 Made, Lamongan District, Lamongan Regency. Class management can affect student learning outcomes 49.14%. Meanwhile, 50.86% is influenced by other factors.